Kemitraan dalam Pengelolaan Objek Wisata Istano Basa Pagaruyung dan Batu Angkek-angkek Kabupaten Tanah Datar Sumatera Barat - Fellacia Suciana; Fitriyah . (Journal of Politic and Government Studies, 2017)
Abstract: One way to succeed of regional autonomy is the development in tourism sector. But a trend happened at this point is unbalanced his roles and lack of cooperation between the government , private and public in developing tourism sector. Hence the study is done aims to understand how a partnership system in the management of tourism objects Istano Basa Pagaruyung and Batu Angkek-Angkek district Tanah Datar West Sumatra. This study using methods the qualitative study descriptive with documentation and interview as a technique of data collection. Target in this research are government , private , owner of tourist objects and people who participate in the management of tourism object Istano Basa Pagaruyung and Batu Angkek-Angkek district Tanah Datar West Sumatra. Partnership is a form of cooperation between two parties or more which aims to improve the ability of an organization in achieving the purpose. Based on the research done overall the problems faced by the Tanah Datar local government partnership related is the problems assets “Land belonging to customary” so as to hinder roads and interest private parties to invest and participate in the management of tourism object. Not only it, but also found the difference process partnership that occurs in the management of tourism object Istano Basa Pagaruyung and Batu Angkek-Angkek. A partnership system in the management of tourism objects Istano Basa Pagaruyung it can be said quite run maximally. Proved the existence of interwoven of cooperation amoung the government , private and the community even though the cooperation in the shape of a contract. Different with the partnerships in the management of tourism objects Batu Angkek-Angkek who is still not maximum. Key words: Tourism, Management, Partnership